Sphingosine kinase inhibition exerts both pro- and anti-atherogenic effects in low-density lipoprotein receptor-deficient (LDL-R−/−) mice - Potì, Francesco; Bot, Martine; Costa, Sara; Bergonzini, Valeria; Maines, Lynn; Varga, Georg; Freise, Hendrik; Robenek, Horst; Simoni, Manuela; Nofer, Jerzy-Roch (Thrombosis and Haemostasis, 2012)
Sphingosine 1-phosphate (S1P), a lysosphingolipid associated with high-density lipoprotein (HDL), contributes to the anti-atherogenic potential attributed to this lipoprotein. This study examined whether a reduction of S1P plasma levels affects atherosclerosis in a murine model of disease. LDL-R−/−mice on Western diet were given ABC294640, an inhibitor of sphingosine kinase (SphK) for 16 weeks. ABC294640 decreased plasma S1P by approximately 30%. However, ABC294640 failed to affect atherosclerotic lesion formation. Plasma triglycerides were reduced whereas total and HDL-cholesterol remained unchanged in course of ABC294640 treatment. ABC294640 increased plasma interleukin (IL)-12p70 and RANTES concentration as well as IL-12p70, RANTES and interferon (IFN)-γ production by peritoneal cells and this was paralleled by enhanced activity of peritoneal and spleen dendritic cells as evidenced by up-regulation of CD86 and MHC-II on CD11c+ cells. As a consequence, increased T-cell activation was noted in ABC294640-treated mice as indicated by enhanced CD4+ splenocyte proliferation, IFN-γ and IL-2 production, and CD69 expression. Con-comitantly, however, ABC294640 treatment redistributed CD4+ and CD8+ cells from blood to lymphatic organs and reduced T-cell number within atherosclerotic lesions. In addition, plasma sVCAM-1, sICAM-1, and MCP-1 levels as well as in vivo leukocyte adhesion and CCL19-induced T-cell penetration into peritoneum were lower in ABC294640-treated animals. In vitro experiments demonstrated reduced VCAM-1 and ICAM-1 expression and lymphocyte adhesion to endothelial cells exposed to ABC294640. In conclusion, treatment with SphK inhibitor leads to both pro- and anti-atherogenic effects in LDL-R−/− mice. As a consequence, SphK inhibition fails to affect atherosclerosis despite significant S1P reduction in plasma.
Keywords: Sphingosine 1-phosphate; high density lipoproteins; inflammation; endothelium; animal models of atherosclerosis